A (des)articulação entre aprendizagem, avaliação e ensino: experiências de professoras no terceiro ano do ensino fundamental - Batista, Natalia (2018)
The theme of this investigation was the assessment of (and to) the learning process, specifically the relationship between learning, assessment and teaching. Its theoretical system of references were the formative assessment and the critical perspectives of assessment in physical education at schools. In this sense, its objective was to identify and analyze learning experiences, assessment and teaching in a 3rd year class of Elementary School, seeking to contribute to the expansion and deepening of the discussions on this theme. The research was developed in two phases: bibliographical and field research; in a predominantly qualitative way, taking into account the social nature of our object. In the bibliographic phase, the discussions about the relationship between the learning process, the assessment and the teaching process were reviewed. The research's theme backgrounds were raised, as well as the studies that approach the concepts of learning, assessment and teaching in education and physical education. The field research phase involved the application of a questionnaire, observations and interviews. After a selection made starting from the answers given to the questionnaire, two teachers of the Teaching System of the City of Uberlândia were chosen - a physical education teacher and a primary school teacher - who taught the same 3rd year class of Elementary School. The treatment, organization and interpretation of the data were guided by the content analysis' conjectures. The data found pointed out limitations in the practices of both teachers regarding the articulation between learning, assessment and teaching. Among them are the dearth of systematic records on the students' performance, and the spontaneous and unplanned nature of the feedback offered to the students, to the detriment of a good, formative and intelligent feedback. The practice of the primary school teacher tended towards the traditional perspectives of teaching and assessment which, for us, moved her away from an assessment that deliberately and systematically aims to improve the learning processes. In the case of the physical education teacher, although there are weaknesses and dissonances regarding the consolidation of a 'formative assessment in physical education at school' - if it is possible to call it that way - it can be noticed that its practice valued the process of knowledge appropriation and it was opened to changes pointed out by the assessment, even if informal. Thus, it can be understood that the evaluative practice of this teacher moves away from traditional perspectives and approaches formative assessment.